2016
DOI: 10.1038/ejhg.2016.84
|View full text |Cite
|
Sign up to set email alerts
|

Protein-altering MYH3 variants are associated with a spectrum of phenotypes extending to spondylocarpotarsal synostosis syndrome

Abstract: Spondylocarpotarsal synostosis syndrome (SCT) is a rare Mendelian disorder (OMIM #272460) characterized by prenatal vertebral fusion, scoliosis, short stature and carpal and tarsal synostosis. SCT is typically known as an autosomal recessive disease caused by variants in the FLNB gene. The genetic basis of the rarer cases of vertical transmissions remains unknown. In two independent families with symptoms related to autosomal dominant SCT, we identified -by exome sequencing -two protein-altering variants in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…Given the recent implication of monoallelic MYH3 variants in some cases of SCTS 6,7 and the suspicion that recessive inheritance underpins SCTS in the families in this study, the maternally transmitted haplotypes in individuals 1 and 2 were also examined. This showed that the top maternally transmitted haplotype that individuals 1 and 2 shared with individual 5 was also inclusive of the MYH3 locus (a 9 cM segment encompassing 28 annotated genes; Figure 2B).…”
Section: Analysis Of Shared Haplotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the recent implication of monoallelic MYH3 variants in some cases of SCTS 6,7 and the suspicion that recessive inheritance underpins SCTS in the families in this study, the maternally transmitted haplotypes in individuals 1 and 2 were also examined. This showed that the top maternally transmitted haplotype that individuals 1 and 2 shared with individual 5 was also inclusive of the MYH3 locus (a 9 cM segment encompassing 28 annotated genes; Figure 2B).…”
Section: Analysis Of Shared Haplotypesmentioning
confidence: 99%
“…5 FLNB was the sole identified locus for SCTS until recent reports of monoallelic variants in MYH3 (MIM: 160720) in families affected by vertical transmission of a SCTS phenotype. 6 An unrelated individual with simplex SCTS and affected members of a three-generation family have also been reported to be heterozygous for protein-altering MYH3 mutations, 7 including an in-frame deletion of a single amino acid and a frameshift variant leading to a presumptive premature termination of protein translation. Before these observations, monoallelic missense MYH3 mutations transmitted in a dominant fashion were also shown to underlie cases of distal arthrogryposis type 8 (DA8, otherwise known as autosomal-dominant multiple pterygium syndrome [MIM: 178110]).…”
Section: Introductionmentioning
confidence: 99%
“…Two families have been reported with autosomal dominant SCT due to variants in MYH3. 3 One family had pure SCT whereas the other family had additional features like joint limitation with pterygia and cardiac disease. However, further clinical and molecular information would be required to describe MYH3-related SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these are immunoglobulin genes, suggesting ethanol effects on bone marrow cells. The strongest downregulation by ethanol (5.2-fold, P = 0.002) was for the gene for Myosin heavy chain 3 (Myh3), of which certain mutations can cause skeletal abnormalities (Carapito et al, 2016). Another gene known to have direct bone effects is Frzb encoding Frizzled Related Protein (Enomoto-Iwamoto et al, 2002).…”
Section: Chronic Alcohol Consumption Reduces Gene Expression Of Majormentioning
confidence: 99%